Adanya korelasi kadar TNF-Î± antara pemeriksaan hapusan lesi dengan pemeriksaan darah perifer pasien stomatitis aftosa rekuren Correlation of TNF-Î± between lesional swab and peripheral blood of mononuclear cell of recurrent aphthous stomatitis patient - Ali Yusran; Erni Marlina; Sumintarti Sumintarti (Journal of Dentomaxillofacial Science, 2011)
Recurrent aphthous stomatitis (RAS)is a common oral mucosal disease in human. This disease affect 20-25% ofpopulation. The etiology remains unclear, but some of cytokine such as TNF-Î± is suspected to contribute in thepathogenesis of RAS. TNF-Î± is commonly measured by PBMC and lesional biopsy. These are invasive method andhigh skilled requirement. Another study used lesional swab to measure this cytokine without correlating the resultwith TNF-Î± measured by PBMC level. This study aimed to asses TNF-Î± level correlation between lesional swab andPBM of RAS patients. The study involved 10 subjects by inclusion criteria. Subjects have lesion swab and PBMCexamined. Samples were analyzed by ELISA method. There is a correlation between lesional swab and PBMC ofTNF-Î± level RAS patients but this correlation did not statistically significant.